Inflation distorts relative prices: Theory and evidence - Klaus Adam; Andrey Alexandrov; Henning Weber (Deutsche Bundesbank, 2024)
We empirically identify the effect of inflation on relative price distortions, using a novel identification approach derived from sticky price theories with time or state-dependent adjustment frictions. Our approach can be directly applied to micro price data, does not rely on estimating the gap between actual and flexible prices, and only assumes stationarity of unobserved shocks. Using the micro price data underlying the U.K. CPI, we document that suboptimally high (or low) inflation is associated with distortions in relative prices. At the level of individual products, the marginal effect of inflation on relative price distortions is highly statistically significant and aligns well with theoretical predictions. Cross-sectional price dispersion turns out to be predominantly driven by movements in the dispersion of flexible prices and thus fails to comove with inflation over time. In contrast, cross-sectional price distortions are found to increase with aggregate inflation.
Keywords: E31; E58; 330